Assessing the impact of sex on high-frequency repetitive transcranial magnetic stimulation's clinical response in schizophrenia: results from a secondary analysis - Campana, Mattia; Schneider-Axmann, Thomas; Wobrock, Thomas; Malchow, Berend; Langguth, Berthold; Landgrebe, Michael; Eichhammer, Peter; Frank, Elmar; Cordes, Joachim; Wölwer, Wolfgang; Gaebel, Wolfgang; Winterer, Georg; et al. (The world journal of biological psychiatry, 2024)
The evidence for repetitive transcranial magnetic stimulation (rTMS) to treat negative symptoms in schizophrenia (SCZ) is increasing, although variable response rates remain a challenge. Subject´s sex critically influences rTMS' treatment outcomes. Females with major depressive disorder are more likely to respond to rTMS, while SCZ data is scarce. Using data from the 'rTMS for the Treatment of Negative Symptoms in Schizophrenia' (RESIS) trial we assessed the impact of sex on rTMS´ clinical response rate from screening up to 105 days after intervention among SCZ patients. The impact of resting motor threshold (RMT) on response rates was also assessed. 157 patients received either active or sham rTMS treatment. No significant group differences were observed. Linear mixed model showed no effects on response rates (all p > 0.519). Apart from a significant sex*time interaction for the positive subscale of the positive and negative syndrome scale (PANSS) scores (p = 0.032), no other significant effects of sex on continuous PANSS scores were observed. RMT had no effect on response rate. In the largest rTMS trial on the treatment of SCZ negative symptoms we did not observe any significant effect of sex on treatment outcomes. Better assessments of sex-related differences could improve treatment individualisation.